Sistem Prosedur Pialang Asuransi Syariah Berbasis Digital di Indonesia - Rusdi Hamka Lubis (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2021)
Identifying the risk of the insured party is the main task of the insurance broker who acts as the insured's representative who has the right to become an intermediary between the insured party and the insurance company. The purpose of this study is to analyze the governance of sharia insurance brokers in identifying the risks that exist to the insured. Qualitative method is a method used to provide a comprehensive picture. The results of this study state that sharia insurance brokers have implemented good corporate governance and have carried out their duties and obligations as representatives implementing the values of governance, risk management and Sharia Compliance. Sharia Insurance Broker professionalism will be felt by the insured if the insurance claim settlement can be done in accordance with the agreement.